Objective Vision-related Indications for Clear and Tinted Football Helmet Visors. Issue 7 (July 2021) - Weise, Katherine K.; Swanson, Mark W.; Galt, Sarah J.; Springer, Daniel B.; Crosson, Jason N.; DeCarlo, Dawn K.; Hale, Matthew Heath; Nicholson, Joshua Ryne; Robinson, James B.
Abstract : SIGNIFICANCE: Football helmet visors are popular among players and may increase safety. However, they may also be costly or impractical, or impair the evaluation of head and neck injury. Determining an objective list of vision-related clinical conditions may help meet risk-benefit ratios while increasing access to care to athletes with special needs. PURPOSE: The purpose of this study was to determine an objective list of vision-related conditions that may benefit from clear and tinted football helmet visor use in athletes. METHODS: After comprehensive dilated eye examinations on 58 Division I collegiate football players at the University of Alabama at Birmingham between February 2017 and June 2018, an expert panel in vision care, sports medicine, and football equipment convened to determine vision-related conditions most important for clear or tinted football helmet visor use. RESULTS: In August 2018, the list drafted by the expert vision and sports medical panel in which a clear football helmet visor might be justified included conditions associated with retinal detachment and unilateral or binocular vision loss as well as high refractive error, refractive surgery, corneal compromise, and other conditions, which would necessitate additional eye protection. Of the 58 players examined, 3 (5%) were determined to have eye conditions that would require a clear visor as deemed by the expert panel, and 3 (5%) were determined to have eye conditions for which a clear visor was recommended. No players met indications for a tinted visor including congenital eye conditions that limit useful vision in daylight or bright-light environments, acquired conditions that may increase light sensitivity, and light-induced systemic conditions. CONCLUSIONS: This objective list of eye and vision-related systemic conditions is intended to mitigate the risk of long-term eye damage and/or vision deprivation. Clear and especially tinted football helmet visors require the sports medicine team to evaluate factors that will maximize the vision, head, and neck health of the athlete while increasing accessibility to sports for individuals with unique abilities. Abstract : Supplemental digital content is available in the text.